Guarded by Two Jaguars : A Catholic Parish Divided by Language and Faith - Hoenes del Pinal, Eric, 1975- (Book collections on Project MUSE., 2022)
"In communities in and around Cobán, Guatemala, a small but steadily growing number of members of the Q'eqchi' Maya Roman Catholic parish of San Felipe began self-identifying as members of the Catholic Charismatic Renewal. Their communities dramatically split as mainstream and charismatic Catholic parishioners who had been co-congregants came to view each other as religiously distinct and problematic "others." In Guarded by Two Jaguars, Eric Hoenes del Pinal tells the story of this dramatic split and in so doing addresses the role that language and gesture have played in the construction of religious identity. Drawing on a range of methods from linguistic and cultural anthropology, the author examines how the introduction of the Catholic Charismatic Renewal movement in the parish produced a series of debates between parishioners that illustrate the fundamentally polyvocal nature of Catholic Christianity. This work examines how intergroup differences are produced through dialogue, contestation, and critique. It shows how people's religious affiliations are articulated not in isolation but through interaction with each other. Although members of these two congregations are otherwise socially similar, their distinct interpretations of how to be a "good Catholic" led them to adopt significantly different norms of verbal and nonverbal communication. These differences became the idiom through which the two groups contested the meaning of being Catholic and Indigenous in contemporary Guatemala, addressing larger questions about social and religious change. "--